Effects of a 10 vs. 20-Min Injury Prevention Program on Neuromuscular and Functional Performance in Adolescent Football Players - Rahlf, Anna Lina; John, Cornelius; Hamacher, Daniel; Zech, Astrid (Frontiers in Physiology, 2020)
Background: Regular injury prevention training is not only effective in reducing sports injury rates, but also in improving neuromuscular and performance-related variables. However, it is currently unknown if this effect can be modified by varying the training dosage. Objective: To compare the effects of two injury prevention programmes with a different training duration on neuromuscular control and functional performance in adolescent football players. Methods: 342 (15.4±1.7 years) male football players from 18 teams were initially included. The teams were cluster-randomized into two intervention groups. Both groups performed an injury prevention programme twice a week during one football season (10 months) using the same exercises but a different duration. One intervention group (INT10, n=175) performed the programme for 10 minutes, while the other intervention group (INT20, n=167) for 20 minutes. At the beginning and end of the season, balance control (Balance Error Scoring System = BESS), jump performance (Squat Jump, Countermovement Jump) and flexibility (Sit and Reach Test, ankle flexibility, hip flexibility) tests were performed. For the final analysis, nine teams with 104 players were considered. Results: Significant group by time interactions were found for the Sit and Reach Test (p<0.001) and ankle flexibility (p<0.001) with higher improvements in the INT20 group. Improvements over the period of one season but no group differences were found for the BESS, Squat Jump and hip flexibility. Conclusion: Within a single training session, performing structured neuromuscular training with a longer duration is more effective than a shorter duration for improving lower extremity flexibility.